In situ synchrotron radiation X-ray scattering study on the effect of a stearic sucrose ester on polymorphic behavior of a new sunflower oil variety - Rincón Cardona, Jaime A. (2014)
The effect of the stearic sucrose ester (SE) S-170 on crystallization behavior and polymorphism of two stearins obtained from a new variety of high stearic high oleic sunflower oil was studied by pulsed nuclear magnetic resonance (p-NMR), small (SAXS) and wide (WAXS) angle X-ray scattering using synchrotron light and differential scanning calorimetry (DSC). p-NMR studies showed that there is always a crystallization temperature below which SE S-170 accelerated crystallization and above which SE S-170 delayed nucleation and growth. The effect of SE S-170 strongly depended on supercooling. It was efficient as a seed for high supercooling (low crystallization temperatures) but this efficiency diminished at low supercooling (temperatures close to the melting point) when few crystals were formed. SAXS and WAXS results demonstrated that depending on crystallization temperature SE S-170 promoted crystallization of α and β forms with more polymorphic similarity and inhibited occurrence of β′ forms especially the β′2 polymorph. However, in some conditions SE S-170 favored crystallization of β′1 polymorph. DSC experiments showed that SE S-170 significantly diminished total melting enthalpies when the effect was a delay in crystallization. For other conditions no significant differences were found in melting temperatures or total melting enthalpies. When stearins were stored at 25 °C, crystallization in the β2 form was promoted. Depending on crystallization temperature, polymorphic forms β′1 and β2 may be obtained as the main polymorphic forms. This is very relevant from the technological point of view. Depending on the application, SE S-170 may help obtain the required polymorphic form: β′1 form for spreads and β2 polymorph for chocolate production.